LEGAL PROTECTION FOR CONSUMERS IN ONLINE SALES TRANSACTIONS: A REVIEW FROM THE INDONESIAN CIVIL CODE - Muhammad Habib Husin; Indah Puja Claudia Damanik; Bartolomeus Marulitua Simanjorang; Viona Francesca Purba; Rama Rizky Septienda Saragih; Dandi Abram Situmorang; Parlaungan Gabriel Siahaan; Sri Hadiningrum (Jurnal Hukum Lex Generalis, 2024)
This research discusses legal protection for consumers in online buying and selling transactions using a normative juridical approach. Through analysis of legal sources, legislation, relevant literature, and transaction data from e-commerce platforms, this study highlights various issues faced by consumers in the e-commerce context, such as product discrepancies, fraud, dispute resolution difficulties, and data security issues. The research also explores the role of the Civil Code (KUH Perdata) and other relevant regulations in providing a framework to protect consumer rights. In the context of breach of contract, the study shows that consumers have rights guaranteed by law to receive compensation if they are affected by a seller's breach of contract. However, challenges such as difficulties in enforcing consumer rights across different jurisdictions remain an issue to be addressed. This research emphasizes the importance of solutions such as cross-border cooperation and online alternative dispute resolution systems in enhancing consumer protection. Keywords: Consumer, Legal Protection, Online Buying and Selling Transactions, Civil Code, Regulation